2014
DOI: 10.1111/bdi.12194
|View full text |Cite
|
Sign up to set email alerts
|

Type and duration of subsyndromal symptoms in youth with bipolar I disorder prior to their first manic episode

Abstract: Objectives To systematically evaluate the prodrome to mania in youth. Methods New-onset/worsening symptoms/signs of ≥ moderate severity preceding first mania were systematically assessed in 52 youth (16.2 ± 2.8 years) with a research diagnosis of bipolar I disorder (BD-I). Youth and/or caregivers underwent semi-structured interviews, using the Bipolar Prodrome Symptom Scale–Retrospective. Results The mania prodrome was reported to start gradually in most youth (88.5%), with either slow (59.6%) or rapid (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 77 publications
(137 reference statements)
4
83
1
1
Order By: Relevance
“…28,29 Several studies have recognized mood lability, major depressive episodes, subsyndromal manic symptoms, a diagnosis of a bipolar spectrum disorder (such as cyclothymia or BD not otherwise specified), and mood-congruent psychotic symptoms as precursors of BD. [30][31][32] On the other hand, in clinical practice, identification of a symptomatic high-risk BD phase is complicated by the complex nature of dimensions of this disorder, by potentially different symptom presentations in children and adolescents, 5,21,33 and by the blurred lines between the prodrome and the disease itself. 34 Retrospective and prospective studies have revealed a pattern of putative prodromal symptoms, of which mood lability/mood swings/cyclothymic features, depressive mood, racing thoughts, irritability, and physical agitation are most commonly reported.…”
Section: Clinical Presentation Of Early Stagesmentioning
confidence: 99%
See 4 more Smart Citations
“…28,29 Several studies have recognized mood lability, major depressive episodes, subsyndromal manic symptoms, a diagnosis of a bipolar spectrum disorder (such as cyclothymia or BD not otherwise specified), and mood-congruent psychotic symptoms as precursors of BD. [30][31][32] On the other hand, in clinical practice, identification of a symptomatic high-risk BD phase is complicated by the complex nature of dimensions of this disorder, by potentially different symptom presentations in children and adolescents, 5,21,33 and by the blurred lines between the prodrome and the disease itself. 34 Retrospective and prospective studies have revealed a pattern of putative prodromal symptoms, of which mood lability/mood swings/cyclothymic features, depressive mood, racing thoughts, irritability, and physical agitation are most commonly reported.…”
Section: Clinical Presentation Of Early Stagesmentioning
confidence: 99%
“…52 Most used either unstructured questionnaires or chart reviews, and failed to assess the onset pattern of the disorder and the symptom severity of the prodromal period, which limits validity. 5 Furthermore, it remains unclear which person (i.e., the patient, a parent, teacher, or peer) is most likely to first notice the prodromal symptoms. 5 Thus, studies that access information regarding prodromal symptoms only from the point of view of patients themselves may be less reliable.…”
Section: Retrospective Designsmentioning
confidence: 99%
See 3 more Smart Citations